A Study of School Absenteeism During Menstruation Amongst Adolescent Schoolgirls in An Urban Area of North India - Nabilal Patavegar, Bilkish; Ahmad, Siraj; Hassan, Syed Belal; Ahmad, Ausaf; Tiwari, Pradeep Kumar (National Journal of Community Medicine, 2024)
Introduction: WHO has defined adolescence period as the phase of life between childhood and adulthood. This study aimed to estimate the percentage of girls absent from school during menstruation, investigate the underlying causes of this absenteeism, and determine the association between school absenteeism and various factors. Methods: In present community-based study, 473 school going adolescent girls studying in 9th to 12th standards were selected by multistage stratified random sampling method. We selected 3 private and 3 government schools. Adolescent girls were interviewed by pretested, predesigned, semi-structured questionnaire for data collection. Results: The mean age of the students was 16.64 ± 1.4 years. 29.2% participants were absent from school during menstruation. Dysmenorrhea was the most prevalent reason for school absence, quoted by 51(37%) of the participants. In present study positive association between school absenteeism and various socio-demographic factors like the type of school, socioeconomic status, mother's education level, access to hygienic menstrual products and health education was observed. Conclusion: Nearly one-third of the girls were absent in school during menstruation. The main reasons for school absenteeism reported by girls were dysmenorrhea, mother's restrictions, fear of staining cloth and difficulty in changing pads in school.